Strategies for carbon reduction and advertising investments in partially centralized supply chains - Weisi Zhang; Jiahao Kong; Wei Zhao; Juanjuan Liu (PLoS ONE, 2026)
Rising concerns about climate change and growing consumer awareness of environmental sustainability have accelerated the adoption of cap-and-trade policies worldwide. This study investigates how different supply chain operation models influence manufacturers’ carbon reduction decisions and retailers’ green advertising strategies. Our analysis reveals that higher carbon trading prices generally stimulate greater emission reduction efforts. However, when both the carbon price and the cost of emission reduction are sufficiently high, further increases in carbon prices may instead weaken firms’ incentives to reduce emissions. We further find that increasing cost-sharing ratios alone does not necessarily improve coordination outcomes. Instead, the effectiveness of coordination depends critically on the structure of cost-sharing. The effectiveness of supply chain coordination hinges on strategic allocation of cost-sharing ratios, specifically, the RC model performs better when carbon reduction cost-sharing is low and advertising cost-sharing is high. When carbon reduction cost-sharing is high, the MC model is preferred under low advertising cost-sharing, whereas the DC model becomes more effective when advertising cost-sharing is high.